Development of high yielding, bacterial leaf blight and blast disease resistant rice (Oryza sativa L.) variety through marker-assisted backcross breeding - Chibuike, Chukwu Samuel (2019)
Rice is an important food crop that serves as a major carbohydrate source for nearly half of the world’s population. Bacteria leaf blight caused by the pathogen Xanthomonas oryzae pv. oryzae (Xoo) is one of the most serious diseases responsible for significant yield reduction in rice. Rice blast disease is caused by the fungal pathogen Magnaporthe oryzae. Both are very destructive diseases of rice in Malaysia and other parts of the world’s major rice growing regions causing considerable yield loss. The main objective of this study was to develop high yielding, bacterial leaf blight and blast disease resistant rice variety for commercial cultivation in Malaysia through marker-assisted backcross breeding. Parental varieties used were Putra-1 which is high yielding and blast resistant, and served as the recipient, and IRRB60 as the donor which is bacterial leaf blight resistant. Fifteen simple sequence repeats (SSR) and functional markers that were reported to be linked to Xoo resistance genes were screened to confirm their polymorphism between the two parents. Also, two SSR DNA-based markers that are linked to blast resistance genes were tested for their polymorphism between the two parents. A total of 472 rice SSR markers were screened out of which 79 polymorphic markers were identified between the two parents. A total of 16.74% level of polymorphism spread across the 12 rice chromosomes was recorded from the 472 markers assessed. The result showed that the number of polymorphic markers per chromosome confirmed ranged from four (chromosomes 10 and 11) to nine (chromosomes 2, 8 and 12). Out of the 72 grown F1 plants, five F1 hybrids were confirmed to carry all the Xoo (Xa21, xa13, xa5, Xa4) and blast (Piz, Pi2 and Pi9) resistance genes. These five progenies were selected for use in the next crossing to produce BC1F1 population. A total of 288 BC1F1 progenies were obtained from a cross between the best F1 progeny and Putra-1. The Chi-square (χ²) result of the six foreground markers segregation analysis showed no significant difference in the BC1F1 progenies from a 1:1 Mendelian segregation ratio. The result indicated a goodness of fit to the single gene model. The mean recurrent parent genome recovery (RPGR) of BC1F1 population was 80.11%. The best progeny in BC1F1 population was BC1F1-38, with the RPGR of 86.40% and the low heterozygous component of 8.70% and reduced donor genome of 4.90%, in addition to very negligible linkage drag. Out of 268 BC2F1 progenies, 14 plants were confirmed to carry all the seven Xoo and blast resistance genes while χ² result of foreground marker segregation showed a goodness of fit to the single gene model. With the result obtained on recurrent parent genome recovery from marker- assisted background selection of BC2F1 after genotyping, coupled with further confirmation through phenotyping, nine best BC2F1 progenies with recurrent parent genome recovery of more than 95.31% were selected. A total of 220 BC2F2 progenies were grown from the nine selected recurrent parent genome recovered BC2F1 lines and furthermore, the final selection was made from homozygous individuals carrying the donor (IRBB60) parent allele with highest recurrent parent genome recovery percentage. The average RPGR recorded at BC2F2 was approximately 96%. Sixteen progenies from the BC2F2 generation were selected as advanced backcross lines. In the F1 progeny, percentage infection recorded ranged from 4.24% to 10.91%. The average percentage infection was 6.35% while the mean disease score was recorded as 1.00. This result showed that the Xoo resistance genes were introgressed into the F1 progenies and as such, resistant to bacterial leaf blight infection. The Xoo and blast resistance genes were re- validated in BC2F2 populations and the selected improved lines proved to be resistant to bacterial leaf blight and blast diseases. The selection using polymorphic tightly linked functional and SSR foreground markers was successfully used to identify BC1F1, BC2F1 and BC2F2 progenies with the targeted alleles. The introgression of dominant (Xa21, Xa4) and recessive (xa13, xa5) Xoo resistance genes as well as blast R-genes (Pi9, Pi2, Piz) were confirmed in the selected BC1F1, BC2F1 and BC2F2 progenies. The high percentage of recurrent parent genome recovery in these populations was an indication of high potentials of marker-assisted backcross breeding in recovering the genomes of the recurrent parent in rice and other cereal crops. The successful pyramiding of seven Xoo and blast resistance genes in the newly developed rice lines will guarantee a broad spectrum and durable resistance. This breeding programme is the very first successful attempt to manipulate the genome of the Malaysian elite rice variety Putra-1 without jeopardising its high yielding characteristic and blast resistance but with additional advantage of Xoo resistance in the newly improved lines. The newly developed rice lines are recommended varieties suitable for commercial cultivation in Malaysia and other rice growing regions.